Pengaruh Topografi Permukaan Panel Surya Terhadap Penyerapan Radiasi Matahari Pada PLTS - Silitonga, Remina; Dalimunthe, Muhammad Erpandi (Politeknik Harapan Bersama Tegal, 2025)
The surface of solar panels plays an important role in the efficiency of solar energy absorption. This study aims to analyze the effect of variations in the surface topography of solar panels on the amount of solar radiation absorbed in the Solar Power Generation (PLTS) system. The method used is experimental by comparing flat, tilted, and optimal horizontal panels under natural lighting conditions. Measurements were carried out with a 50 Wp solar panel for five consecutive days from 08.00 to 16.00 WIB. Data include measurements of voltage, current, power, and energy under three different topographic conditions. The results show that the tilt of the panel according to geographic latitude provides the highest efficiency in solar energy absorption. This study confirms that the design of surface topography can improve the performance of solar panels.